Designing an Energy Community Operator : Capabilities for citizen engagement in Nordic case studies - Valta, Jussi; Leite, Emilene (Routledge, 2025)
Cities and municipalities have a central role in creating more sustainable and resilient energy systems. Investing in energy infrastructure in an urban context requires acceptance from citizens, and a promising model, energy communities (ECs), has been developed to achieve this. Connecting incumbents in the energy sector with the newcomers requires new operating models, but there is a lack of actors with the capabilities required to implement them. This chapter studies the capabilities and activities of EC operators required to engage citizens in the energy transition. Based on four case studies covering the Finnish and Swedish contexts, we demonstrate that integrating citizens into the complex creation process of ECs has its challenges. The key conclusion is that the mechanisms for citizen participation and behavioural change matter only if the operator can create viable models and align the interests of various actors. Due to the early stage of EC regulatory frameworks, this requires institutional, organisational and social capabilities. By making the operator's capabilities explicit, it is possible to develop such actors and create new partnerships.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|